2019
DOI: 10.1073/pnas.1813486116
|View full text |Cite
|
Sign up to set email alerts
|

Preventing harassment and increasing group participation through social norms in 2,190 online science discussions

Abstract: Theories of human behavior suggest that people’s decisions to join a group and their subsequent behavior are influenced by perceptions of what is socially normative. In online discussions, where unruly, harassing behavior is common, displaying community rules could reduce concerns about harassment that prevent people from joining while also influencing the behavior of those who do participate. An experiment tested these theories by randomizing announcements of community rules to large-scale online conversation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(69 citation statements)
references
References 28 publications
4
64
0
1
Order By: Relevance
“…Interventions have been highly successful in changing social norms concerning drinking and driving, 18 energy conservation, 19 , 20 tax compliance, 21 intergroup prejudice, 22 and bullying and harassment. 23 , 24 Likewise, research has illustrated that entire countries can tighten norms that have become too loose. 3 In what has become known as the Youth in Iceland study, parents and local governments joined together to successfully tighten social norms to reduce alcohol and drug abuse, which has been regarded as a model programme in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions have been highly successful in changing social norms concerning drinking and driving, 18 energy conservation, 19 , 20 tax compliance, 21 intergroup prejudice, 22 and bullying and harassment. 23 , 24 Likewise, research has illustrated that entire countries can tighten norms that have become too loose. 3 In what has become known as the Youth in Iceland study, parents and local governments joined together to successfully tighten social norms to reduce alcohol and drug abuse, which has been regarded as a model programme in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…An example implementation of CivilServant is a recent experiment that was done in a Reddit community with 13 million subscribers. An announcement about a new community rule was randomly assigned to some of the new members in an online science discussion forum (Matias, 2019). Presenting the announcement informed new participants about the community's rules: no jokes, no abusive content, and so on.…”
Section: Experimenting In Social Media Governancementioning
confidence: 99%
“…Using standard machine learning approaches (Mattos et al, 2017;Gauci et al, 2018), such systems can continuously "nudge" the design, with the aim of maximizing outcomes desired by the platform owner. Matias and Mou (2018) suggested that a similar testing approach might be useful in the implementation of online governance policies (Matias, 2019).…”
Section: Optimization Of Feedback Systems With Fsgmentioning
confidence: 99%
“…9 Community rules can be viewed as an instantiation of injunctive norms that characterize the perception of what most people approve or disapprove of (vs. descriptive norms that characterize the perception of what most people do) in the focus theory of normative conduct [11]. Prior research has studied the effect of exposure to (violating) such norms on community-level or discussion-level behavior [25][26][27]. For instance, through randomizing announcements of community rules to discussions in the Science subreddit, Matias [25] shows that making community rules visible prevents unruly and harassing conversations.…”
Section: Enforcement and Maintenance Of Injunctive Norms: A Broader Lmentioning
confidence: 99%
“…Prior research has studied the effect of exposure to (violating) such norms on community-level or discussion-level behavior [25][26][27]. For instance, through randomizing announcements of community rules to discussions in the Science subreddit, Matias [25] shows that making community rules visible prevents unruly and harassing conversations. In comparison, our focus is on the effect of moderator actions that enforce injunctive norms on individual users.…”
Section: Enforcement and Maintenance Of Injunctive Norms: A Broader Lmentioning
confidence: 99%